ChemInform Abstract: Production of Hydrogen by Electrocatalysis: Making the H—H Bond by Combining Protons and Hydrides. Issue 19 (13th May 2014) - Bullock, R. Morris; Appel, Aaron M.; Helm, Monte L.
Abstract Review: [100 refs.